TELAAH FILOSOFIS KONSEP MURABBI DALAM TRADISI TASAWUF AL-JUNAYD DAN URGENSINYA DALAM PEMBENTUKAN GURU IDEAL - Munzirin, Al (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
The crisis of the ideal educator figure in the modern era has become a critical issue in contemporary education. Teachers are no longer seen merely as transmitters of knowledge but are increasingly expected to be holistic educators who guide both the intellect and the soul of learners. In this context, the concept of murabbi found in Islamic Sufi tradition offers a meaningful framework for reinterpretation. This study focuses on the thoughts of Al-Junayd al-Baghdadi, a prominent classical Sufi, who formulated a spiritual and ethical model of the murabbi. A philosophical-hermeneutical approach is employed to analyze classical Sufi texts and their relevance to modern teacher education systems. The study identifies four key pillars of the ideal murabbi figure according to Al-Junayd: profound knowledge (al-‘ilm), spiritual piety (al-wara’), exemplary conduct (al-uswah), and wisdom (al-hikmah). These components form a holistic spiritual-pedagogical framework capable of addressing the growing need for character education in the digital age. The findings imply the necessity to reform teacher education curricula to incorporate Sufi values and to foster educators who are not only methodologically skilled but also spiritually and ethically grounded. Al-Junayd’s concept of the teacher as murabbi offers a transformative vision in responding to the current value disorientation in education.